Scaling law for baryon coupling to its current and its possible applications - Dey, Jishnu; Dey, Mira; Frederico, T.; Tomio, Lauro [UNESP] (World Scientific Publishing, 1997)
The baryon coupling to its current (λB), in conventional QCD sum rule calculations (QCDSR), is shown to scale as the cubic power of the baryon mass, MB. Some theoretical justification for it comes from a simple light-cone model and also general scaling arguments for QCD. But more importantly, taken as a phenomenological ansatz for the present, this may find very good use in current explorations of possible applications of QCDSR to baryon physics both at temperature T = 0, T ≠ 0 and/or density ρ = 0, ρ ≠ 0. © World Scientific Publishing Company.